American Transcendentalist’s Conceptions of Self: Comparison Among Emerson, Thoreau And Whitman - Sutanto, Dian Natalia (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2017)
American Transcendentalism was a unique movement in the country’s history as it had a vitalizing effect on the development of American identity and fostered the development of American democracy, liberalism, art and literature. Its basic tenet is the belief on the dignity of human as the manifestation of the divine. Emerson, Thoreau and Whitman, the three main exponents, share this basic tenet. They believe that iindividual virtue and happiness depend on self-realization which is achieved through self reliance on one’s intuition and imagination, rather than on social conventions and religious dogma. However, these three figures disagree on what specific course of actions to actualize individual virtue and happiness. Thoreau believes that to achieve the highest virtue, one must detach oneself from one’s dependency on materiality and practice simple, solitary life in nature. Different from Thoreau, Whitman views that flesh was also necessary for self-actualization, and thus must not be neglected. Emerson’s position, on the other hand, is somewhat caught between the two. Different from Thoreau who emphasizes the primacy of one’s duty to oneself to attain highest virtue through solitary life in nature, Emerson concept’s of self realization is balanced by the duty to others through voluntary participation in social reform. Unlike Whitman who celebrates carnality as the source of human virtue, Emerson’s view is more austere.